Association of psoriasis with chronic kidney disease and end-stage renal disease: a systematic review and meta-analysis - Jing, Xu; Zhuyuan, Wen; Aijun, Chen; Jianxia, Xiong; Kun, Huang; Ping, Wang (Frontiers in Medicine, 2023)
Background and objective Previous studies have shown that patients with psoriasis are at higher risk of developing chronic kidney disease (CKD) and end-stage renal disease (ESRD) compared with general population; however, data on the differences in the occurrence of CKD and ESRD between patients with psoriasis and non-psoriatic controls are limited and inconsistent. The aim of this study was to carry out a comparison of the probability of suffering CKD and ESRD in patients with or without psoriasis by conducting a meta-analysis of cohort studies. Methods Cohort studies on PubMed, Web of Science, Embase and Cochrane Library by March, 2023 were searched for. The studies were screened according to pre-established inclusion criteria. Hazard ratios (HRs) and a 95% confidence intervals (CIs) for the renal outcomes among patients with psoriasis were calculated using the random-effect, generic inverse variance method. Subgroup analysis was related to the severity of psoriasis. Results A total of seven retrospective cohort studies were included, including 738,104 psoriasis patients and 3,443,438 non-psoriasis subjects, published from 2013 to 2020. Compared to controls without psoriasis, patients with psoriasis had an increased risk of CKD and ESRD, with pooled hazard ratios of 1.65 (95% CI, 1.29–2.12) and 1.37 (95% CI, 1.14–1.64), respectively. Besides, the incidence of CKD and ESRD is positively correlated with the severity of psoriasis. Conclusion This study showed that compared to patients without psoriasis, patients with psoriasis, especially those with severe psoriasis, had a significantly increased risk of developing CKD and ESRD. Considering the limitations of this meta-analysis, more high-quality and well-designed studies are needed in the future to validate our findings.